Pharmacological evaluation of clinically relevant concentrations of (2R, 6R)-hydroxynorketamine. (15th July 2019) - Shaffer, Christopher L.; Dutra, Jason K.; Tseng, Wei Chou; Weber, Mark L.; Bogart, Luke J.; Hales, Katherine; Pang, Jincheng; Volfson, Dmitri; am Ende, Christopher W.; Green, Michael E.; Buhl, Derek L.
Abstract: Ketamine is a rapid-onset antidepressant whose efficacy long outlasts its pharmacokinetics. Multiple studies suggest ketamine's antidepressant effects require increased α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR)-dependent currents, which have recently been exclusively attributed to its N -methyl-d -aspartate receptor-inactive metabolite (2 R, 6 R )-hydroxynorketamine ((2 R, 6 R )-HNK). To investigate this AMPAR-activation claim further, we estimated and evaluated preclinically and clinically relevant unbound brain HNK concentrations ( C b, u ). (2 S, 6 S )-HNK and (2 R, 6 R )-HNK were novelly synthesized, and their neuropharmacokinetic profiles were determined to project relevant C b, u . Using concentrations (0.01–10 μM) bracketing the pertinent cross-species C b, u, both compounds' AMPAR modulation was assessed in vitro by electrophysiological recordings and GluA1 surface expression. Neither (2 S, 6 S )-HNK nor (2 R, 6 R )-HNK bound orthosterically to or directly functionally activated AMPARs. (2 R, 6 R )-HNK failed to evoke AMPAR-centric changes in any electrophysiological endpoint from adult rodent hippocampal slices. Conversely, time- and concentration-dependent increases in GluA1 expression occurred only with (2 R, 6 R )-HNK (≥0.1 μM at ≥90 min). The (2 R, 6 R )-HNK concentrations that increased GluA1 expression are consistent with its maximal C b, u (0.92–4.84 μM) at reportedly efficacious doses of ketamine or (2 R, 6 R )-HNK in mouse depression models, but ≥3-fold above its projected maximal human C b, u (≤37.8 ± 14.3 nM) following ketamine's clinically antidepressant infusion. These findings provide insight into the observed AMPAR-affecting (2 R, 6 R )-HNK concentrations versus its exposures attained clinically at an antidepressant ketamine dose. To optimize any clinical study with (2 R, 6 R )-HNK to fully assess its translational pharmacology, future preclinical work should test (2 R, 6 R )-HNK concentrations and/or C b, u of 0.01–0.1 μM to parallel its projected human C b, u at a clinically antidepressant ketamine dose.